Idiopathic infantile arterial calcification in two siblings: failure of treatment with diphosphonate. Issue 2 (August 1990) - Stuart, G; Wren, C; Bain, H
Abstract : Two siblings with idiopathic infantile arterial calcification are reported. The fetal and postnatal echocardiographic features were a large pericardial effusion, thickened pulmonary and aortic valves, poor pulsation of the descending aorta, and calcification of the great vessels. In one patient calcification was first detected at 33 weeks' gestation. Despite treatment with disodium etidronate both children died.